Designing Competency-Based Career Paths: Organizational Strategies for Retaining High-Performing Employees - Mushthofa, Muhammad Abduh; Handoyo, Seger (Psikostudia : Jurnal Psikologi, 2023)
It is very important for organizations today to acquire and retain high performing employees. This is because the knowledge and competence they have is the capital for the organization to maintain a competitive advantage. PT. MPM, a distributor company for Honda motorcycles, is currently facing a situation where employees who resign complain that the company's career development policies are unclear. This research is an organizational development assessment and intervention. The method used in this study is the research and development method in which organizations produce products to improve organizational performance. In this research, the resulting product is a competency-based career path. This competency-based career path is expected to answer the employee's need for a transparent career development policy. On the other hand, this career path can also be the basis for organizations in implementing the competency development required by a position.Sangat penting bagi organisasi di masa ini untuk memperoleh dan mempertahankan karyawan dengan kinerja yang tinggi. Hal ini dikarenakan pengetahuan dan kompetensi yang mereka miliki merupakan modal bagi organisasi untuk mempertahankan keunggulan kompetitif. PT. MPM sebuah perusahaan distributor motor merk Honda saat ini menghadapi situasi di mana karyawan yang resign mengeluhkan kebijakan pengembangan karir di perusahaan yang dirasa tidak jelas. Penelitian ini merupakan asesmen dan intervensi pengembangan organisasi. Metode yang digunakan dalam penelitian ini adalah metode research and development di mana organisasi menghasilkan produk untuk peningkatan kinerja organisasi. Dalam penelirtian ini, produk yang dihasilkan berupa jalur karir berbasis kompetensi. Jalur karir berbasis kompetensi ini diharapkan dapat menjawab kebutuhan karyawan akan kebijakan pengembangan karir yang transparan. Di sisi lain, jalur karir ini juga dapat menjadi dasar bagi organisasi dalam implementasi pengembangan kompetensi yang dibutuhkan oleh sebuah jabatan.